PENGARUH MODEL INKUIRI TERBIMBING DENGAN PENDEKATAN ENGINEERING DESIGN PROCESS TERHADAP HASIL BELAJAR SISWA SMP - Ammy Alya Amelia; Pramudya Dwi A. P.; Rusdianto Rusdianto (ScienceEdu, 2024)
Science learning in junior high school is still based on text book center and teacher center learning which is indicated by various research on the difficulty of learning science and the low independence of students to hone critical thinking skills and low learning outcomes. This is because students tend to memorize learning materials and lack of critical thinking exercises and activities. Based on this, improving the learning outcomes of junior high school students requires a way that requires students to think critically in the field of science, one of which uses a guided inquiry learning model with an engineering design process approach. This study aims to examine the effect of guided inquiry learning model with engineering design process approach on learning outcomes of junior high school students. This research is a quantitative study with a quasi experimental research design and uses a posttest-only nonequivalent group design. The subjects in this study were students of SMP Negeri 14 Jember class VII. The average value of post-test learning outcomes showed that the experimental class value was higher (72.51) than the control class (67.68). The results of data analysis of learning outcomes were analyzed using the Independent sample t-test and showed a significance level value of 0.012 (<0.05), which means that there is an average difference between the experimental class and the control class. So that it indicates the effect of using the guided inquiry learning model with an engineering design process approach on the learning outcomes of junior high school students.